Assess patient’s techniques and knowledge towards insulin pen injection at Outpatient Pharmacy in Hospital Batu Pahat - Ahmad Arshad, Ahmad Akmal (2012)
Diabetes mellitus (DM) is a metabolic disorder caused by absolute or relative lack of insulin. The objectives of this study are to assess the insulin injection technique in patient with diabetes and to investigate their knowledge and awareness involving the insulin injection. This is a prospective study that was carried out in the Outpatient Pharmacy, Hospital Batu Pahat during office hour (8am-5pm). Prescriptions were screened and patients were selected based on certain criteria. Then, patients were asked by using questionnaire and scores were given. The data were collected and recorded in Microsoft Excel (version 2007). The Statistical Package for the Social Science Version 17.0 (SPSS) was used to analyze the result. The result obtained from the project shows that most of the subjects were still lack of knowledge towards insulin pen injection. Moreover, majority of them does not have a good insulin injection technique. Recounsel and giving pamphlet can be done to improve their knowledge and technique. Besides that, a more appropriate research can be done in the future to assess back patients knowledge after those initiatives had been done.